ASEAN sebagai Instrumen Adaptasi Singapura terhadap Globalisasi - Dian Mutmainah; Nindi Rachmawati (Jurnal Transformasi Global, 2014)
Abstract             This paper addresses the ability of Singapore to adapt to global economic challenges through regionalism. Using Moravcsik’s liberal intergovernmentalist theory, it investigates how Singapore consistently exerts its orientation to implement trade liberalization and economic integration in ASEAN. Focusing on one of three areas of national preferences, this paper found that Singapore has been dynamically adapted to external challenges. These capacities in turn influenced its external strategies. Instead of seeing its neighbours in ASEAN as competitors, Singapore views their comparative advantages as part of its economic strategies. This gives Singapore a good (and convincing) position to lead other ASEAN members to deeper and wider economic integration.             Keywords: regionalism, ASEAN, Singapore, globalization